Consumer Empowerment in Transportation Sector - Megawati Simanjuntak; Raisha Ulfa Saniyya (Universitas Prasetiya Mulya, 2021)
Awareness of rights and obligations as a consumer became one of the problems faced by consumers. One way to increase consumer awareness is to provide access to consumer education through media used by consumers. This article aimed to identify and analyze the effect of socio-demographic characteristics and consumer education media toward consumer empowerment on public transportation. This research used a cross-sectional study through an online survey of 100 users of public transportation. Data were analyzed using multiple regression analysis. The results showed that the consumer empowerment index is 44.56 and categorized as capable level. Also, female, early-aged adults (18 - 40 years), high education, employee, income range from IDR 2 000 000 to IDR 3 000 000 per capita per month, and an urban area were the most empowered consumers. In addition, employment status and media of consumer education positively and significantly influenced consumer empowerment. https://doi.org/10.21632/irjbs.14.1.1-12